The governance of marine restoration: insights from three cases in two European seas. (27th October 2020) - van Tatenhove, Jan P. M.; Ramírez‐Monsalve, Paulina; Carballo‐Cárdenas, Eira; Papadopoulou, Nadia; Smith, Chris J.; Alferink, Lieke; Ounanian, Kristen; Long, Ronan
Abstract : This article analyses three different cases of assisted marine restoration in Europe to understand how governance and legal aspects enable or constrain marine restoration in practice. The aim of this article is to enhance understanding of the enabling and constraining conditions of the governance of marine ecological restoration. To understand the governance of marine restoration, we use the concepts of governance arrangement and institutionalization . A marine restoration governance arrangement consists of different coalitions of public and private actors, who—through their different ways of conceptualizing and understanding the problem (discourses)—try to influence and design the marine restoration activities and initiatives, the managing of often shared, limited resources, and defining rules of the game (on different levels). Institutionalization refers to the production and reproduction of governance arrangements. This article gives insight in the governance arrangements of three cases: artificial habitat as in the Rigs‐to‐Reefs debate, in the context of North Sea oil and gas decommissioning, and restoration of key sedimentary and hard natural habitats of the fan mussel ( Pinna nobilis ) and red coral ( Corallium rubrum ) cases in the Mediterranean. The analysis shows how discourses shape the arrangements that currently govern the decommissioning of obsolete oil and gas structures in the North Sea, and the protection and management of two emblematic and endangered species in the Mediterranean. Based on the analysis we formulated enabling and constraining conditions for the institutionalization of "active restoration" governance arrangements, resulting in recommendations for how to strengthen restoration in policies and legislation.